Integrative and mind-body approaches to law enforcement professional wellness - Julie Eitzen; Stefanie Holden; Lauray MacElhern; Cassandra Vieten (Frontiers in Public Health, 2026)
Background Law enforcement (LE) personnel have one of the most stressful jobs, and LE in the United States face a particular set of stressors that merit investigation. LE personnel regularly encounter some of the worst aspects of human nature, which elevates their risk for mental and physical health problems. This population needs viable, accessible methods for stress management and healthy lifestyle education. Integrative and mind-body practices represent one such solution. This structured review aims to assess the effectiveness and promise of integrative health interventions studied in US LE, provide researchers with a resource for conducting future studies, and draw attention to the need for wellness resources for LE personnel in the US. Methods PubMed was searched for studies published in 2000 or later that examined an integrative or mind-body health intervention with US LE personnel, including yoga, mindfulness, diet, exercise, or any combination thereof. We reviewed the measures, outcomes of interest, and intervention methodology used across studies. Results We identified 21 eligible studies encompassing six major intervention categories: mindfulness, self-regulation, wellness programs, sleep, yoga, and detoxification approaches. Outcomes of interest fell into 10 categories: stress and burnout, mental health, physiological and physical, anger and aggression, job satisfaction and performance, sleep, positive psychology, cognitive, health behaviors, and social. We also compiled the measures used across studies into two overarching categories: survey and qualitative measures, and physical/physiological measures (e.g., sleep duration, strength, BMI). Conclusions The results of this review can be used to inform future studies on this population and help formulate wellness programs for LE. Mindfulness interventions generally improved mental health, burnout, mindfulness, and organizational stress; the single study measuring aggression found a significant improvement. Self-regulation interventions improved some physical/physiological outcomes but not others, with no change in sadness, anger, or anxiety. Wellness program interventions showed promise for improving health behaviors, particularly eating habits, tobacco use, strength, and avoidance coping. Yoga was beneficial for global mood and perceived stress. Results were mixed both between and within studies of the same intervention type. Future research with this population should focus on determining the most efficient and effective interventions for US LE personnel.